2009
DOI: 10.1038/npp.2009.71
|View full text |Cite
|
Sign up to set email alerts
|

A Transcranial Magnetic Stimulation Study of the Effects of Cannabis Use on Motor Cortical Inhibition and Excitability

Abstract: Active compounds in cannabis such as tetrahydrocannabinol (THC) interact with the inhibitory neurotransmitter d-aminobutyric acid (GABA) but little is known about the functional effects of cannabis on human cortical brain processes. Therefore, the aim of the study was to investigate whether patients with chronic cannabis use demonstrate abnormalities in cortical inhibition or excitability. In all, 42 chronic cannabis using subjects (divided into heavy and light using subjects) and 19 controls were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 38 publications
4
28
0
1
Order By: Relevance
“…Comorbid cannabis abuse was suggested to potentiate the reduced short interval cortical inhibition and enhanced intracortical facilitation observed in patients with first-episode schizophrenia. This finding is consistent with a those of a previous study by Fitzgerald and colleagues 55 reporting that heavy and light users of cannabis demonstrated significantly decreased short interval cortical inhibition compared with healthy controls. Taken together, these studies provide evidence that schizophrenia is associated with cortical inhibition deficits in the motor cortex.…”
Section: Schizophreniasupporting
confidence: 83%
“…Comorbid cannabis abuse was suggested to potentiate the reduced short interval cortical inhibition and enhanced intracortical facilitation observed in patients with first-episode schizophrenia. This finding is consistent with a those of a previous study by Fitzgerald and colleagues 55 reporting that heavy and light users of cannabis demonstrated significantly decreased short interval cortical inhibition compared with healthy controls. Taken together, these studies provide evidence that schizophrenia is associated with cortical inhibition deficits in the motor cortex.…”
Section: Schizophreniasupporting
confidence: 83%
“…SICI was attenuated in cannabis users, and one of the interpretations was that GABA A receptor-mediated synaptic transmission was inhibited by cannabinoids in the cortex (Fitzgerald et al, 2009). Inhibition of GABA A receptor-mediated synaptic transmission by a cannabinoid in the human cortex in vitro, as demonstrated in our study at the monosynaptic level, may be the basis of the effect observed in vivo by Fitzgerald et al (2009).…”
Section: Discussionmentioning
confidence: 58%
“…Such decreases in CB1Rs could lead to alterations in GABA release, thus disrupting the ability of neural networks to generate synchronized neural oscillations. Indeed, a transcranial magnetic stimulation (TMS) study by Fitzgerald et al (2009) found that both heavy and light users of cannabis exhibit disruptions in short interval cortical inhibition that is indicative of altered GABA function. A final potential mechanism relates to the effect of cannabis on neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%